Economic and Societal Losses Due to Environmental Impacts on Forestry Productivity - Noriko Sato; Tetsuhiko Yoshimura (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
After successful government-led afforestation projects, what are the challenges for forest management in the face of climate change in East Asia? This reprint presents studies from the natural and social sciences related to forest conservation, engineering, disaster sociology, and forest policy in China and Japan. The papers cover a range of topics, including forest owners' attitudes, forest resource utilization, evaluation of forestry mechanization and forest roads, characteristics of damage from torrential rains, resilience of rural communities, economic transformation, and others.
Keywords: 320; Yangtze River Delta; forest resources abundance; economic development; ESG; sustainable management; corporate social responsibility (CSR); non-financial disclosure; emerging market; key state-owned forest area; system coupling; ecological construction; economic transformation; grey relational analysis (GRA); extreme value analysis; daily rainfall; floods; rainfall-induced landslides; regional frequency analysis; station-year method; Kyushu region; CO2 emission; forestry; Gifu Prefecture; input–output analysis; renewable energy; ripple effect; eco-efficiency; sustainable development; forestry resources; New Scheme of Forest Management; Forest Management Law; private forest; small-scale forestry; typology of forest owners; Japan; bearing capacity; road construction method; roadbed strength; soil; spur road; forest road failure; streamside; stream crossing; zero-order basin; relative risk; seisan shinrin kumiai; ninka chien dantai; common property resource; developed countries; external policy influence; forest management activities; local landscape; observation; depopulation; municipal government; local identity; revitalization; outsiders; collaboration; resilience; small-scale forest road; UAV; Structure from Motion (SfM); earthwork volume; under tree canopy; productivity; harvesting system; processor tower yarder; combined machine productivity; combined labor productivity; afforestation; under-utilization; forestry operation; clearcutting; economic losses; societal losses; rural community; disaster-resilient forestry; East Asia